Dual energy X-ray absorptiometry in morphological asymmetry assessment among field hockey players - Krzykala, M. (Journal of Human Kinetics, 2010)
Every sports discipline is characterized by specific movements which are symmetric or asymmetric. Field hockey belongs to a asymmetric activity. There is suspicion that players, who use more frequently one side of the body during training or the game, have also side-to-side morphological diversification. The main aim of the study is to determine the degree of asymmetry which manifests itself in somatic characteristics. The analysis was done among twenty competitive Polish male field hockey players. All athletes undertook total body Dual X-Ray Absorptiometry (DXA) scans, which divided the body into anatomic segments: arms, trunk, and legs. Professional field hockey participation showed significantly enhanced muscle mass and higher bone mineral density on the left side of the body. The present data should help better understand complicated morphology of highly trained athletes with more comprehensive and accurate approach to their anthropometrical description.